Exhaled nitric oxide in symptomatic children at preschool age predicts later asthma. Issue 4 (18th February 2013) - Singer, F.; Luchsinger, I.; Inci, D.; Knauer, N.; Latzin, P.; Wildhaber, J. H.; Moeller, A.
Abstract Background Prediction of asthma in young children with respiratory symptoms is hampered by the lack of objective measures applicable in clinical routine. In this prospective study in a preschool children cohort, we assessed whether the fraction of exhaled nitric oxide (FeNO), a biomarker of airway inflammation, is associated with asthma at school age. Methods At baseline, IgE and eosinophils were measured in the blood, and FeNO was measured offline in 391 children aged 3–47 months with lower airway symptoms. We developed an asthma predictive index (API) including high FeNO as major criterion. At follow‐up, primary outcome was physician‐diagnosed asthma based on standardized interviews in those children reaching school age (n = 166). Results FeNO was significantly elevated in those children with later asthma (68/166) as compared to children not developing asthma. Median (IQR) FeNO was 10.5 (6.6–17.2) vs 7.4 (5.3–10.3) ppb. Per 5 ppb FeNO increase, the odds ratio (95% CI) for asthma increased by 2.44 (1.61–3.70) without changing when adjusting for confounders. Using the new API, children scored at risk had 58.0% probability for later asthma, whereas the negative predictive value was 78.2%, which was comparable to the classical API. Conclusions In this cohort of high‐risk preschool children, elevated FeNO is associated with increased risk for school‐age asthma. The new API including FeNO identifies children at risk of later asthma comparably to the classical API, but does not require blood sampling.